Peculiar near-band-edge emission of polarization-dependent XEOL from a non-polar a-plane ZnO wafer - Lin, Bi-Hsuan; Wu, Yung-Chi; Chen, Huang-Yeh; Tseng, Shao-Chin; Wu, Jian-Xing; Li, Xiao-Yun; Chen, Bo-Yi; Lee, Chien-Yu; Yin, Gung-Chian; Chang, Shih-Hung; Tang, Mau-Tsu; Hsieh, Wen-Feng (Optics express, 2018)
Polarization-dependent hard X-ray excited optical luminescence (XEOL) was used to study not only the optical properties but also the crystallographic orientations of a non-polar a-plane ZnO wafer. In addition to a positive-edge jump and extra oscillations in the near-band-edge (NBE) XEOL yield, we observed a blue shift of the NBE emission peak that follows the polarization-dependent X-ray absorption near-edge structure (XANES) as the X-ray energy is tuned across the Zn K-edge. This NBE blue shift is caused by the larger X-ray absorption, generating higher free carriers to reduce the exciton-LO phonon coupling, which causes a decrease in the exciton activation energy. The extra oscillations in XANES and XEOL as the polarization is set parallel to the c-axis is attributed to simultaneous excitations of the Zn 4p - O 2pπ -bond along the c-axis and the bilayer σ-bond, whereas only the σ-bond is excited when the polarization is perpendicular to the c-axis. The polarization-dependent XEOL spectra can be used to determine the crystallographic orientations.